PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA SD/MI - Adesta Syafitria; Adinda Dwi Ariesta; Romsiah Berlianna; Siti Fatimah; Trianita Melya Putri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
One of the things that teachers need to prepare to support the delivery of learning materials and the success of an education is audio-visual learning media. Audio visual media are media that have elements of sound and elements of images that can be seen and heard. The purpose of this study is to determine the application of audio-visual media in learning activities, the advantages and benefits of audio-visual media in increasing student learning interest and student enthusiasm in teaching and learning activities in class. This research uses qualitative methods used in this study is a qualitative approach in the nature of a literature study, the techniques used by literature review and data sources to be obtained later come from Mendeley and google scholar. The result of this study is that the use of audio-visual media in the teaching and learning process can make learning interesting and not boring, so this media is highly recommended by teachers in the teaching process, and students are more interested in listening and paying attention to the material taught. by the teacher. Therefore, the use of audio-visual media is very effective in capturing content or subject matter because it can generate motivation and interest in learning among elementary / MI students.